Ketidakpastian Hukum Terhadap Penundaan Eksekusi Pidana Mati - Vic S., Binsar Jon; Rusman, Rusman; Margaretha Tjhia, Kimico; Maria, Indri (Pascasarjana UDA, 2023)
This study aims to examine the legal uncertainty that occurs during the waiting period for the execution of the death penalty, which is an important issue in the Indonesian criminal justice system. This study highlights the urgency of clearer and more comprehensive legal regulations to address the legal vacuum related to the execution waiting period limit which is not regulated in detail in Article 98 of Law No. 1 of 2023 concerning the Criminal Code (KUHP). The uncertainty in this waiting period leads to unauthorized delays and has the potential to disrupt the basic principles of punishment, such as legal certainty, justice, and the effectiveness of the deterrent effect. Through a normative legal approach, this study provides a solution to the legal vacuum by suggesting an update or revision to Article 98 which can regulate in detail the procedures for implementing the death penalty and its waiting period, with the aim of ensuring fair and efficient implementation in accordance with the principles of a state of law based on the 1945 Constitution and applicable legal norms.